On some western Palaearctic species of the genus Omalium Gravenhorst, 1802 (Coleoptera: Omaliinae: Omaliini) - Shavrin, Alexey V. (Zootaxa, 2025)
Taxonomic and faunistic notes for 13 species of the genus Omalium Gravenhorst, 1802 of the western Palaearctic region are provided. Two species are redescribed and illustrated: North European O. muensteri Bernhauer, 1901 and Iberian O. asturicum Fauvel, 1900. Two new synonymies are proposed: O. allardi Fairmaire & Brisout de Barneville, 1859 = O. vaulogeri Fauvel, 1905 syn. nov., and O. funebre Fauvel, 1871 = O. deubeli Bernhauer, 1915 syn. nov. Lectotypes for O. muensteri and O. deubeli are designated. The habitus of the types of O. vaulogeri and O. deubeli, and, in addition, the aedeagus of the holotype of O. vaulogeri are illustrated. The aedeagus of O. muensteri is illustrated for the first time. First records are provided for the following eight species: O. asturicum from Badajos, Málaga and Granada (Spain), O. funebre from Moldavia, O. italicum Bernhauer, 1902 from Algeria, O. rugatum Mulsant & Rey, 1880 from Crimea (Ukraine), and Bolu and Ordu (Turkey), O. wunderlei Zanetti, 2002 from Izmir, Bolu, Niğde and Van (Turkey), O. cinnamomeum Kraatz, 1857 from Bulgaria, Hatay (Turkey), Lebanon and Syria, O. falsum Eppelsheim, 1889 from Tehran (Iran), and O. rivulare (Paykull, 1789) from Ordu, Yozgat, Tokat and Van (Turkey).